Sekolah Ramah Lalu Lintas sebagai Upaya Pembinaan Kesadaran Berlalu Lintas untuk Anak Usia Sekolah Dasar - Afidah, Irma Nur; Nisfa, Nia Lailin; Parlina, Bella Putri (LP3M IAIFA Kediri, 2025)
This community service program aims to foster a sense of responsibility, caution, and concern for personal and public safety among elementary school students. Furthermore, the program is expected to serve as a traffic education model that can be sustainably implemented in schools with the support of teachers, parents, and the community. The implementation employed the Asset Based Community Development (ABCD) approach, consisting of the stages of Discovery, Dream, Design, and Destiny. The Discovery stage involved identifying school assets and students’ initial understanding of traffic rules. In the Dream stage, teachers and students collaboratively formulated a vision of a traffic-friendly school. The Design stage produced training modules and interactive activities such as simulations, helmet-wearing practice, traffic sign recognition, and educational games. Finally, the Destiny stage was realized through participatory training at SD Negeri 02 Cepogo, followed by evaluation and the development of a traffic safety handbook to ensure program sustainability. The results showed significant improvements in students’ knowledge and skills in recognizing traffic signs, practicing proper riding ethics, and applying safety measures such as helmet use and appropriate riding capacity. The program also received strong enthusiasm from students, teachers, and parents, which further supports its sustainability. Thus, this community service program not only enhances traffic safety awareness among students but also has the potential to become a replicable traffic education model for other elementary schools and madrasah.